Manifestations of War in the Works of the Artist Muhammad Mahraldin - Shaymaa hazim qabel (Basrah Arts Journal, 2024)
This research is concerned with studying (Manifestations of war in the works of the artist Muhammad Mahraldin). It is divided into four chapters. The first chapter is to state the problem of the research that is represented by the question (Are there effects of war on the drawings of the artist (Muhammad Mahraldin)? And how did he depict Manifestations of war in his painted works?) and its importance and need for it. Then identifying the goal of the research in (revealing Manifestations of war in the works of the artist Muhammad Mahraldin), followed by establishing the boundaries (temporal, spatial, and thematic), and then the terms related to the title. The second chapter identified two substantive sections within the theoretical framework, according to what reading the research requires, is as follows (the first topic: embodiment of war and its manifestations in Iraqi art, the second topic: the embodiment of Manifestations of war in Iraqi art). The third chapter is devoted to research procedures, by clarifying the studies society, and the chosen sample (4 samples), the observational analysis tool, and identifying its methodology, and analyzing the sample. The fourth chapter includes: 1. The artist’s psychological influence appears through the structural formulations of the painting in making it a virtual environment by interweaving abstract shapes. The conclusions include: 1. It becomes clear that the artist Mahraldin was influenced by the products of the wars that took place in Iraq and the pressures they represented on the artists.